Nursing: a spiritual perspective - Long, Ann (Nursing ethics, 1997)
This article explores and examines the fundamental need for nurses to include the promotion of the spiritual dimension of the health of human beings as well as the physical, mental and social facets if they truly wish to engage in holistic care. The author attempts to define the phenomenon of spirituality, aware of the dilemma that many individuals face when thinking and reflecting on this very personal and intangible issue.To be spiritual is to become fully human, the article argues, and the reverse is also true. Spirituality in health is inextricable in each person’s search for the discovery of the truth about self and the meaning and purpose of life. Healthy communities are the product of healthy individuals who sow spiritual seeds such as unconditional positive regard, acceptance, respect and dignity for the benefit and advancement of individuals and humankind as a whole.The global nature of the phenomenon of spirituality is also shown by using examples of people who demonstrate compassion and communion with other human beings, in other countries in times of suffering, war and disaster. Compassion and empathy is expressed and experienced for victims of earthquakes that happen miles from home and far removed from personal or religious beliefs. Yet at such times we are all connected in the tapestry of life by our own human spirituality and earthiness.Abstract themes like compassion and justice are treated in the text within the context of spirituality. The author argues that being just and fair means that all patients have the right to achieve spiritual healing regardless of their belief systems, culture or creed. The works of some spiritual philosophers are used to reflect on this integral aspect of human caregiving.Historical symbols of spirituality are examined. The need for nurses to explore and reflect on the paradoxical concepts involved in their own spirituality is highlighted. Nurses are the essential providers of care and, therefore, the paper argues, guardians of that essential humanity that ensures that patients never become less than full human beings, whatever their condition, faith, culture or belief, or whoever they may be. The author contends that this responsibility is uniquely essential to being a nurse.